A comprehensive review of properties of the biocompatible thin films on biodegradable Mg alloys. (1st January 2023) - Rajan, S Thanka; Arockiarajan, A
Abstract: Magnesium (Mg) and its alloys have attracted attention as biodegradable materials for biomedical applications owing to their mechanical properties being comparable to that of bone. Mg is a vital trace element in many enzymes and thus forms one of the essential factors for human metabolism. However, before being used in biomedical applications, the early stage or fast degradation of Mg and its alloys in the physiological environment should be controlled. The degradation of Mg alloys is a critical criterion that can be controlled by a surface modification which is an effective process for conserving their desired properties. Different coating methods have been employed to modify Mg surfaces to provide good corrosion resistance and biocompatibility. This review aims to provide information on different coatings and discuss their physical and biological properties. Finally, the current withstanding challenges have been highlighted and discussed, followed by shedding some light on future perspectives.